THE CONTRIBUTION OF ISLAMIC PSYCHOTHERAPY TO MENTAL HEALTH - ., Musrifah; Anita, Dewi Evi; Wibowo, Hamid Sakti (TAWASUT, 2024)
Considering that humans are a unity of soul and body, of course many of the principles of mental health science come from sciences that study the soul and body, such as psychology and psychology. Mental health with the aim of healing uses the principles of psychological and emotional adjustment obtained from scientific discoveries in the fields of medicine, psychology, sociology and other knowledge. The problem in this research is what is the concept of mental health in the era of globalization (Study of Islamic psychotherapy analysis)? To be more focused, this research was formulated to answer what the nature and characteristics of mental health are, what mental health is like in the Islamic psychotherapy approach, and what the characteristics and characteristics of a healthy mentality are in the modern era. This research aims to describe the nature and characteristics of mental health. characteristics of mental health, mental health in the Islamic psychotherapy approach, as well as descriptions, characteristics of healthy mental health in the modern era.Keywords: Mental Health, Islamic Psychotherapy